(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Structural design is a very important domain to learn for the architectural students withoutwhich their unique and original thinking cannot be carried through to completion. While the students‟emphasis is more on creative aspects in design studios and they fail to realize the relevance of variousaspects of structures to their creativity. The academic curriculum and pedagogy here plays a major partin establishing the correlation between both architectural and structural aspect of building design in theminds of the students. This research is done to assess the teaching pedagogy used to solve theproblems faced by students while studying structural design in their curriculum. This paper hasidentified the pedagogical helping tools to bridge the gap between the issues and solutions tounderstand the structural design subjects by the architectural students. Additionally this paper has alsotried to recommend innovative pedagogical techniques which can change the outlook of architecturalstudents while studying structural design from the beginning.